Short-term efficacy of enzalutamide in treatment of patients with abiraterone-resistant metastatic castration-resistant prostate cancer - MEI Jingchang, SU Xiaonan, YAO Yu, GUAN Fengju, ZHANG Guiming (精准医学杂志)
Objective To investigate the short-term efficacy and safety of enzalutamide in the treatment of patients with abiraterone-resistant metastatic castration-resistant prostate cancer (mCRPC). Methods A total of 31 patients with abiraterone-resistant mCRPC who attended The Affiliated Hospital of Qingdao University from December 2020 to April 2022 were enrolled as subjects, and all these patients received treatment with enzalutamide after developing resistance to abiraterone. Related data were collected, including the response or resistance to abiraterone before enzalutamide treatment, prostate-specific antigen (PSA) level at baseline, PSA response, time to PSA progression, radiographic progression, and adverse reactions after enzalutamide treatment. The univariate and multivariate Cox regression analyses were used to identify the risk factors for PSA progression after enzalutamide treatment. Results Among the 31 patients during follow-up, 12 (38.7%) had PSA response, 4 (12.9%) had stable PSA, and 15 (48.4%) had no response to PSA. There were 22 patients (71.0%) with PSA progression and 20 (64.5%) with radiographic progression. Of all patients, 28 (90.3%) experienced adverse reactions, mainly weakness and anorexia, and 2 patients (6.5%) withdrew from drug therapy due to adverse reactions; 7 patients (22.5%) experienced tumor-related death. The univariate Cox analysis showed that compared with the patients with a serum PSA level of ≤20 μg/L at the time of diagnosis, the patients with a serum PSA level of >20 μg/L had a higher risk of PSA progression, and the multivariate Cox regression analysis showed that a higher serum PSA level at the time of a confirmed diagnosis of prostate cancer was an independent risk factor for the prognosis of patients. Conclusion Enzalutamide has a certain short-term efficacy in some mCRPC patients resistant to abiraterone, but the majority of patients still face the risk of disease progression. Weakness and anorexia are common adverse reactions, but most adverse reactions are relatively mild and can be tolerated by most patients.